Micronutrient status and disease state in patients with inflammatory bowel disease - Stull, Kacie Michelle Mallon (My University, 2025)
Inflammatory Bowel Disease (IBD) is a collective term for chronic conditions that cause gastrointestinal inflammation. Micronutrient deficiencies are common in individuals with IBD and are thought to play a significant role in both the pathogenesis and progression of the disease. Despite the high prevalence of micronutrient deficiencies, nutritional screening is not a standard component of IBD care, limiting effective disease management and patient outcomes. This study aimed to describe individual patterns in dietary intake, micronutrient status, and disease burden among adults with IBD. This case series examined the micronutrient levels of adults (n=7) with IBD through laboratory blood tests. Micronutrient intake was evaluated using the Food Frequency Questionnaire (FFQ) developed by the Nutrition Assessment Shared Resource (NASR) at Fred Hutchinson Cancer Center. Disease-related disability was measured using a modified Inflammatory Bowel Disease Disability Index (IBD-DI), and inflammation was assessed via C-reactive protein (CRP) levels. Vitamin D deficiency was the most common concern observed in three cases. Two of the three participants had elevated CRP levels, indicating a relationship between inflammation and low vitamin D. Elevated B12 levels were noted in two cases, and one participant had low folate intake and deficiency. Iron and magnesium intake were associated with lower laboratory values, though no participants were iron deficient. IBD-DI scores indicated minimal disability despite micronutrient deficiencies and elevated CRP. Trends suggested a link between inflammation and lower nutrient levels. This study emphasizes the need for monitoring micronutrient status in IBD patients and calls for further research with larger sample populations to better understand the complex relationships between micronutrient levels, dietary intake, inflammation, and disease-related disability.
Keywords: Inflammatory bowel disease; Micronutrient levels; Ulcerative colitis; Crohn's disease; Dietary intake